The pit - Norris, Frank, 1870-1902 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Pit: A Story of Chicago" by Frank Norris is a novel published in 1903. Set in the frenetic wheat trading pits of the Chicago Board of Trade, it follows Laura Dearborn's marriage to Curtis Jadwin, a successful businessman. As Jadwin becomes obsessed with wheat speculation, his attention shifts from his wife to the intoxicating thrill of the market. Left increasingly alone, Laura faces her own temptations while her husband risks everything in pursuit of wealth and power. This second installment of Norris's unfinished Epic of the Wheat trilogy explores marriage, ambition, and the consuming nature of greed. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Pit_(Norris_novel)
Release date is 2003-08-01
Produced by Charles Aldarondo. HTML version by Al Haines.
Keywords: Didactic fiction; Psychological fiction; Domestic fiction; Married people -- Fiction; Chicago (Ill.) -- Fiction; Wheat trade -- Fiction